Benefits of participatory plant breeding (PPB) as exemplified by the first-ever officially released PPB-bred sweet potato cultivar - Gibson, R.W.; Mpembe, I.; Mwanga, Robert O.M. (Cambridge University Press, 2011)
NASPOT 11 is a recently released sweet potato cultivar, bred by participatory plant breeding (PPB) in Uganda. It is already grown extensively by farmers who call it Tomulabula. In on-farm and on-station yield trials, Tomulabula yielded as well as the researcher-bred variety NASPOT 1 and sometimes more than the local landraces Dimbuka and New Kawogo, which have also been released. Farmers were asked to what extent Tomulabula, NASPOT 1 (the most popular station-bred cultivar in Uganda) and the local indigenously bred cultivar they were currently growing satisfied 52 attributes previously identified by farmers as beneficial in sweet potato. Those cultivars whose breeding involved farmers (Tomulabula and the local cultivar) were perceived mostly to satisfy a broad range of attributes (i.e. had few ‘Very Bad’ scores) while those which involved researchers (Tomulabula and NASPOT 1) were the most frequently rated as ‘Very Good’ for specific attributes. Instances were observed and accounts given of how Tomulabula is sold at a premium and how it had improved farmers’ lives. These outcomes are attributed to PPB combining the strengths of farmers and researchers. The involvement of the Ugandan National Sweetpotato Program (UNSP) ensures that planting material will be conserved and also available in adequate amounts for official distribution.